Innovation in Bali Tourism Destination Marketing: Utilization of Digital Technology and Social Media in Bali, Focusing on Badung Regency - Susanti, Putu Herny; Rahmawati, Rahmawati; Amir, Firlie Lanovia; Febianti, Febianti (IJCS: International Journal of Community Service, 2024)
Tourism in Indonesia, especially in Bali, has become a major economic pillar for the government and local communities. However, the rapid growth of the tourism industry also brings challenges, especially in facing increasingly fierce competition in the digital era. Innovation in tourism destination marketing is very important to attract tourist interest and maintain Bali's position as a leading destination. This article highlights the rapid changes in the tourism industry due to advances in digital technology and social media, with a focus on Badung Regency as the main tourism location in Bali. The use of social media as a promotional and marketing tool for tourist destinations, especially in Indonesia, is also an important highlight. The research results note significant growth in the use of social media in Indonesia, which can be used to boost the tourism sector. The digital tourism strategy was also highlighted as an effective effort to promote Indonesia's tourism potential through various platforms. Innovative breakthroughs in the tourism business in Bali, such as online booking, transportation applications, and experience-based tours, are also in the spotlight in the face of technological advances. This article aims to provide information and analyze how innovation in tourism destination marketing can be carried out in Badung Regency, Bali, through the use of digital technology and social media. Education and training of local stakeholders is considered important to increase their effectiveness in marketing and take advantage of existing opportunities. Through community service methods, this article emphasizes the importance of an integrated approach in the use of digital technology and social media. The research results show that marketing strategies via social media can increase the attractiveness of destinations, increase tourist engagement, and have a positive impact on the local economy.